Physical, Chemical and Mechanical Characterization of a Prototype Insulating Material Based on Eucalyptus Bark Fiber - Rojas Herrera, Carlos; Cea Lemus, Mara; Rosas Diaz, Felipe Esteban; Cardenas Ramirez, Juan Pablo (Revista IEEE América Latina, 2018)
In recent years it has become evident that homes have low levels of thermal insulation, which in southern Chile, translates into excessive combustion of biomass by the residential sector to condition housing, generating high levels of air pollution which is harmful to society. It is for this reason that the development of sustainable materials, from natural and local raw material enhances its attractiveness. The present project evaluated the possibility of developing a material from natural fibers from forest waste, which can be found in abundance in the IX region of Araucania. Several physical, chemical and mechanical characterization tests were applied, as well as an optimization model for the elaboration of optimal prototypes, where a decrease in the thermal conductivity of the material could be generated, which finally reached 0.040 (W/mK), which is comparable with the properties of an Expanded Polystyrene type IX. Finally, the optimal conditions for the processing of a prototype are identified, which was analyzed morphologically using scanning electron microscopy (SEM) and thermally, by thermogravimetric analysis (TGA).